Geological subdivision of the Lützow–Holm Complex in East Antarctica: From the Neoarchean to the Neoproterozoic - Dunkley, Daniel J.; Hokada, Tomokazu; Shiraishi, Kazuyuki; Hiroi, Yoshikuni; Nogi, Yoshifumi; Motoyoshi, Yoichi (Polar Science, 2020)
We summarize U–Pb age data for the Lützow–Holm Complex (LHC) in East Antarctica and propose the following geological subdivisions based on protolith ages, along the coast of Dronning Maud Land from southwest to northeast: the Innhovde Suite (INH, 1070–1040 Ma) composed mainly of felsic orthogneiss; the Rundvågshetta Suite (RVG, 2520–2470 Ma), mostly felsic orthogneiss with minor mafic and metasedimentary gneisses; the Skallevikshalsen Suite (SKV, 1830–1790 Ma), felsic to mafic orthogneiss with abundant dolomitic marbles, calc-silicates and other metasediments; the Langhovde Suite (LHV, 1100–1050 Ma), mostly felsic orthogneiss with minor mafic and calc-silicate gneisses; the East Ongul Suite (EOG, 630 Ma), with various orthogneisses and metasediments; and the Akarui Suite (AKR, 970–800 Ma) with diverse orthogneisses and paragneisses. The oldest crustal components of the LHC lie in the southern part of Lützow–Holm Bay, and consist of late Neoarchean and Paleoproterozoic protoliths to charnockites and enderbites that dominate the Rundvågshetta and Skallevikshalsen Suites. This older domain is surrounded by gneisses and granulites with late Mesoproterozoic to early Neoproterozoic protolith ages, including the Innhovde Suite and the Langhovde Suite. The Akarui Suite contains diverse orthogneisses with Neoproterozoic protoloiths, and the youngest unit is the East Ongul Suite with protolith ages of ~630 Ma. Cape Hinode, located geographically within the Akarui Suite, underwent high-grade metamorphism at ~960 Ma that is much older than that which produced the gneisses and granulites of the surrounding LHC (~600–520 Ma). Cape Hinode is therefore exotic, independent of the surrounding LHC, and defined as the “Hinode Block”. The boundaries proposed in this paper are largely consistent with those inferred from magnetic anomalies, gravity anomalies, and bedrock topographical data. journal article